Lógica formal da lógica aristotélica ao cálculo sentencial bivalente - Soares, Edvaldo (Editora Oficina Universitária, 2023)
The aim of the work is to address the central themes of Classical Logic, from Aristotle's syllogistic to the calculation of first-order predicates. Emphasis will be placed on the construction of formally valid structures and on the science of validating arguments. For that, the following plan will be followed: In the first one, we present some preliminary concepts (historical and philosophical) in relation to logic. In the second part we will approach the traditional logical logic, with special emphasis on the construction of syllogisms (Categorical and Hypothetical) and, in the third, the foundations of propositional knowledge and knowledge of first order predicates. We warn that this is a work for the uninitiated and, as such, at the risk of making some inaccuracies, the least technical language possible will be used.